Nghiên cứu sự truyền dẫn proton trong các chất điện li dẫn proton dạng polyme gel trên cơ sở poly(metylmetacrylat) - Thức, Nguyễn Văn; Cẩm Hả, Nguyễn Thị (Vietnam Journal of Chemistry, 2016)
The proton-conducting gel electrolytes were prepared by doping of poly(methyl methacrylate) (PMMA) with phosphoric acid solutions in dimethylformamide (DMF). Conductivity activation energy was weak dependent concentrations of polymer; it lies within about7 kJ/mol. At the same time, the viscosity activation energy changed within 14-23 kJ/mol. This difference can be explained by Grotthuss type mechanism of conductivity. On the basis of IR and H-NMR spectroscopy, we reported that phosphoric acid molecules formed hydrogen bonds with PMMA and MTMA, which was the model of a PMMA single fragment. Possible schemes of proton transfer in the gel have been proposed with the solvent and the polymer matrix Keywords. Mechanism, proton, Grotthuss, gel, polymer.